Aggregation‐induced emission luminogens for in vivo molecular imaging and theranostics in cancer - Peili Cen; Jiani Huang; Chentao Jin; Jing Wang; Yen Wei; Hong Zhang; Mei Tian (Aggregate, 2023)
Abstract Cancer is one of the most fatal diseases for decades. Aggregation‐induced emission luminogens (AIEgens) have been recently used as molecular imaging or therapeutic agents in cancers, due to the advantages of large Stokes shift, high quantum yield, great biocompatibility, and strong photostability. AIEgens can specifically target different types of cancer via diverse targeting strategies. AIEgen‐based fluorescence imaging, especially near‐infrared imaging, demonstrated deep penetration and suitable signal‐to‐noise ratio, which allows reliable in vivo cancer imaging. Combined with other imaging modalities, AIEgen‐based multimodal imaging could provide multidimensional cancer hallmarks from different perspectives. In addition, AIEgen‐based phototherapy can be used for photodynamic therapy and photothermal therapy, which facilitate ablation of cancer cells with good biosafety and high therapeutic effects in vivo. AIEgens nanoparticles fabricated with some specific chemicals, drugs, or siRNA, could display synergistic therapeutic effects for cancers. This paper comprehensively describes the current status and future perspectives of AIEgens, which have showed a great potential for the future preclinical and clinical translation on in vivo molecular imaging and theranostics in cancer.